2014
DOI: 10.1039/c4ta03044c
|View full text |Cite
|
Sign up to set email alerts
|

High supercapacitor and adsorption behaviors of flower-like MoS2nanostructures

Abstract: Uniform 3D flower-like MoS2nanostructures were successfully synthesized through a facile two-step hydrothermal method and had high supercapacitor and adsorption behaviors toward Rhodamine B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
156
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(164 citation statements)
references
References 32 publications
5
156
0
Order By: Relevance
“…Graphene-analogous MoS 2 also possesses large specific surface area due to its unique SeMoeS layered structure similar to "sandwich": there is a hexagonal layer of Mo held between two S layers, existing strong covalent bonding between MoeS while weak van der Waals interaction between SeS. Moreover, the planar charge transportation properties can be enhanced because of the two-dimensional (2D) electron-electron correlations among Mo atoms [8]. Remarkably, MoS 2 has higher theoretical capacity compared to graphite and higher intrinsic fastionic conductivity compared to its oxides [11,14].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Graphene-analogous MoS 2 also possesses large specific surface area due to its unique SeMoeS layered structure similar to "sandwich": there is a hexagonal layer of Mo held between two S layers, existing strong covalent bonding between MoeS while weak van der Waals interaction between SeS. Moreover, the planar charge transportation properties can be enhanced because of the two-dimensional (2D) electron-electron correlations among Mo atoms [8]. Remarkably, MoS 2 has higher theoretical capacity compared to graphite and higher intrinsic fastionic conductivity compared to its oxides [11,14].…”
Section: Introductionmentioning
confidence: 98%
“…Recently, layered transition metal dichalcogenides (TMDs) have attracted intensive attention, which have been applied in a variety of fields [5], such as energy storage [6], hydrogen evolution reaction [7], adsorbents [8], solid lubricants [9], and so on. From the structural point of view, molybdenum disulfide (MoS 2 ) is one typical member of the TMDs family, which has been shown to be a promising electrode material for the SCs due to its high theoretical specific capacitance with the layered structure analogous to graphite [10e13].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 132 reported 3D flower-like MoS 2 nanostructures obtained through a two-step hydrothermal treatment of MoO 3 nanorods. This pure MoS 2 showed a high specific capacitance of 168 F g À1 at 1 A g À1 in 1 M KCl solution.…”
Section: Applications In Energy Storage Devicesmentioning
confidence: 99%
“…While the 1T-polytype 33 of MoS2 has demonstrated high capacitance, electrodes made from the 2H-polytype of a number of TMDs have shown lower performances. [66][67][68][69][70] Because the aim of this work is not to demonstrate high-performance supercapacitors but to explore the effect of nanosheet dimensions on the performance of supercapacitor electrodes, we have opted to use size-selected 2H-WS2 nanosheets as a model system. An EDLC stores energy by localising non-Faradic charges at an electrode-electrolyte interface.…”
Section: Dependence Of Double Layer Capacitance On Nanosheet Sizementioning
confidence: 99%